Unfaithfulness of Elida Wangel Reflected at Henrik Ibsen's The Lady From The Sea 1888 a Psychoanalytic Approach - Djati, Erlangga; , Dr. Phil. Dewi Chandraningrum, M.Ed; , Siti Fatimah, S.Pd., M.Hum (2016)
ABSTRACT ERLANGGA DJATI. A320110044. UNFAITHFULNESS OF ELIDA WANGEL REFLECTED AT HENRIK IBSEN'S THE LADY FSEA (1888): A PSYCHOANALYTIC APPROACH. Research Paper. School of Teacher Training and Education, Muhammadiyah University of Surakarta. February, 2016. The problem of this study is "How is the the personality of Ellida Wangel reflected in Henrik Ibsen's Lady from the sea play?". The objective of this study to analyze Lady from the sea based on Structural analysis and the to analyze Lady from the sea play based on Psychoanalytic perspective. The researcher employs qualitative method. The writer uses two data sources: primary and secondary. The primary data source is about The primary data sources is the textplay itself. Then, the secondary data sources are from other sources such as essay, articles, biography of Henrik Ibsen, Internet and other relevant information. The method of data collection is library research and the technique of data collection is descriptive technique. Based on the anaylisis, the researcher get some conclusions. Ellida is a strong-willing and free character. She considers that every decisions of her live should be based on her own free will. Ellida Wangel has being mentally unfaithful toward her husband. The stranger man, the man who previously had a relationship with Ellida, has a mysterious power against Ellida and she manifests it toward her continuous affection of the sea. Despite she is never physically cheating with the stranger, she always dreams that she is belong to him along with the sea. Keywords: Psychoanalytic, Lady from the sea, Infidelity, Unfaithfulness